A new approach for recognition of human emotions - Karthigayan, M.; Mohd Rizon, Muhamed Juhari; Sazali, Yaacob; Nagarajan, R. (Institut Teknologi Bandung, 2009)
Organized by Institut Teknologi Bandung, Indonesia, 29th - 30th November 2006 at Bandung, Indonesia.